1993
DOI: 10.3109/10520299309104670
|View full text |Cite
|
Sign up to set email alerts
|

Fixation for the 1990's: a Review of Needs and Accomplishments

Abstract: Neutral buffered formalin (NBF) has been the standard fixative in histopathology for many decades; however, new technologies and increasing time constraints have made this common fixative less widely applicable. The attributes of universal and ideal fixatives are reviewed and compared with those of NBF. On the strength of a growing body of literature and experience in the histopathology field, zinc formalin solutions are recommended as a functional replacement for NBF. Zinc formalin permits better morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 15 publications
0
40
0
2
Order By: Relevance
“…178 The basic mechanism of fixation with formaldehyde is the formation of addition products (adducts) between the formalin and uncharged reactive amino groups (-NH or NH 2 ) that eventually will form cross-links. 75 The formation of methylol adducts inactivates nucleases and proteases. 261 Once the addition product (reactive hydroxymethyl compound) is formed, additional cross-links develop.…”
Section: Fixationmentioning
confidence: 99%
“…178 The basic mechanism of fixation with formaldehyde is the formation of addition products (adducts) between the formalin and uncharged reactive amino groups (-NH or NH 2 ) that eventually will form cross-links. 75 The formation of methylol adducts inactivates nucleases and proteases. 261 Once the addition product (reactive hydroxymethyl compound) is formed, additional cross-links develop.…”
Section: Fixationmentioning
confidence: 99%
“…With the recognition that formalin fixation causes major chemical changes in antigens by unknown mechanisms, several attempts were made to modify the methods of fixation, and a variety of modified fixatives have been proposed for preservation of certain antigens Dapson 1993;Elias 1990;Colvin et al 1988;DeLellis 1988;Larsson 1988;Hopwood 1985). However, no ideal fixative has been found that can be used universally in IHC.…”
mentioning
confidence: 99%
“…Acredita-se que o sistema avidina-biotina utilizado no presente trabalho tenha maior sensibilidade do que o sistema peroxidase-anti-peroxidase (Bullock e Petrusz, 1989). Além disso, o uso de outro fixador que não o formaldeído é de difícil implementação na rotina de laboratório de diagnóstico histológico (Dapson, 1993).…”
Section: Methodsunclassified